Process of diagnosis and treatment of chronic cough in children at primary hospitals - Shen, Hua-Qin; Zhang, Yan-Han; Zhang, Jing; Sheng, Qiu-Ming (Frontiers in Pediatrics, 2022)
Objective: This study aimed to establish a process for the diagnosis and treatment of chronic cough in children suitable at primary hospitals and improve the treatment efficacy rate and improve health economic indicators. Methods: Children who visited the Department of Pediatrics, Affiliated Zhou Pu Hospital of the Shanghai Health Medical College from January to December 2021 were randomly assigned to the intervention group (n = 206), in which the diagnosis and treatment process proposed here was applied, and a control group (n = 211) that did not use the current process and delayed the diagnosis and treatment with previous experience. Patients were followed up and data were collected at weeks 0 (time of enrollment), 2, 4, 8, and 12 to evaluate the efficacy rate and clinical value. Results: (1) No significant differences were detected between the two groups in baseline characteristics, including gender, age, duration of cough (weeks), history of allergy in children and parents, and smoking of family members living in the same household (p > 0.05); (2) During the follow-up, all cough symptom scores of the intervention group were lower than the control group. Additionally, at week 12, the treatment efficacy rate of the intervention group (91.70%) was significantly higher than the control group (69.20%) (p < 0.05); (3) The quality of life of children in both groups at week 12 was improved compared to the first visit. However, the total score of the intervention group was significantly higher than the control group (p < 0.05); (4) At week 12, the referral rate was significantly lower in the intervention group (11.17%) than in the control group (21.33%); (5) The intervention group was better than the control group for the mean monthly medication costs, number of days on errors in childhood, and number of days mistakenly worked by family members at week 12 (p < 0.05). Conclusion: The current process of diagnosis and treatment of chronic cough in children at primary hospitals can improve the effective diagnosis and treatment rate, the quality of life, and other parameters, with good effectiveness and feasibility.